قياس تراكيز الرادون في المياه السطحية والجوفية لذراع دجلة والثرثار وحساب الجرعة المؤثرة السنوية باستعمال كاشف الاثر النووي CR-39 - حيدر, لينا مجيد; توفيق, ندى فاضل; مهدي, خالد هادي (Al-Nahrain Journal of Science, 2018)
The aim of this research is to measure radon concentration in surface and under ground water for selected location around Tigris theraa using CR-39 track detector.The selected area is arable land and accounts the main reference of vegetables and fruits for Baghdad city, so the selected regions for surface water were from the initial of Tigris theraa and around under ground water.The radon concentration was determined using natural exposure for two month. The results show that the radon concentration in surface water range from (6.89 to 1.07 Bq/l) and for under ground water from (4.06 to 1.41 Bq/l), the results show that the radon concentration in surface water is greater than ground water. The average annual effective dose in stomach was (25.5-5.6 mSv/yr), in lanch (18.8-2.9 mSv/yr) and in the whole body (54.5-8.4 mSv/yr( for the surface water, and for the ground water, the average annual effective dose in stomach was (21.3-14.1 mSv/yr(,in lanch (11.1-7.1 mSv/yr) and in the whole body (32.1-20.5mSv/yr).